Nahwa Tahdid al-Alaqah baina al-Ulum al-Syar'iyyah wa al-Ulum al-Ijtima'iyyah, Nazrah Tarikhiyyah Fikriyyah - Laith Su'ud Jassum al-Qaisi dan Iman Muhammad Abbas (Buletin Al-Turas, 2007)
Defining the relationship between the islamic sciences and the social Sciences has been an issue of controversy in the intellectual discourse in the Muslim world especially since the end of the ninteen century. this paper is an attempt to explore the historical background of this debatable issue which goes back to the late days of Ottoman calipathe and to identify the way muslim thinkers and Ulama rsponded to the incoming sciences and literature from the west, which ranges from those who were aware of the realities in dealing with the intellectual invasion and incoming cultural influences, to those who welcomed what they perceived as "enlightenment", and those who adopted an extreme objectional position to any western thought. agreeing on a precise definition of the relation between the islamic and social sciences is another aspect of this controversy. some would prefer the "islamization of knowledge" concept, others see the solution inthe integration of those two group of scholars go back to the "Ta'sil" methodology in dealing with any new human sciences. in this paper the researchers porpose what we think as important conditions and prerequisties of any islamization, integration, or Ta'sil process, further more the methodology and the practical means and were of such attempts.